Managing fragmented database in distributed database environment / Ainul Azila Che Fauzi ... [et al.] - Che Fauzi, Ainul Azila; Wan Abdul Rahman, Wan Fariza; Fauzi, Auni; Weigelt, Florian (Unit Penerbitan UiTM Kelantan, 2021)
One of the mechanisms for managing data is replication since it improves data access and reliability. However, the amount of various data grows rapidly since technology is widely available at a low-cost. Problem arises when the transactions only work with a part of the database, not as a whole.This paper will discuss about a technique called database fragmentation. Fragmentation in distributed database is very useful in terms of usage, reliability and efficiency. Handling fragmented database replication becomes a challenging issue to administrators since the distributed database is scattered into split replica partitions or fragments. We address how to build a reliable system by using a distributed database fragmentation algorithm. The result shows that managing database replication with fragmentation will help a transaction to work with the specific part of the database rather than the entire database.